Relationship Between Sinus Rhythm Late Activation Zones and Critical Sites for Scar-Related Ventricular Tachycardia. (April 2015) - Irie, Tadanobu; Yu, Ricky; Bradfield, Jason S.; Vaseghi, Marmar; Buch, Eric F.; Ajijola, Olujimi; Macias, Carlos; Fujimura, Osamu; Mandapati, Ravi; Boyle, Noel G.; Shivkumar, Kalyanam; Tung, Roderick
<x xml:space="preserve">Abstract</x> Background— It is not known whether the most delayed late potentials are functionally most specific for scar-related ventricular tachycardia (VT) circuits. Methods and Results— Isochronal late activation maps were constructed to display ventricular activation during sinus rhythm over 8 isochrones. Analysis was performed at successful VT termination sites and prospectively tested. Thirty-three patients with 47 scar-related VTs where a critical site was demonstrated by termination of VT during ablation were retrospectively analyzed. In those who underwent mapping of multiple surfaces, 90% of critical sites were on the surface that contained the latest late potential. However, only 11% of critical sites were localized to the latest isochrone (87.5%–100%) of ventricular activation. The median percentage of latest activation at critical sites was 78% at a distance from the latest isochrone of 18 mm. Sites critical to reentry were harbored in regions with slow conduction velocity, where 3 isochrones were present within a 1-cm radius. Ten consecutive patients underwent ablation prospectively guided by isochronal late activation maps, targeting concentric isochrones outside of the latest isochrone. Elimination of the targeted VT was achieved in 90%. Termination of VT was achieved in 6 patients at a mean ventricular activation percentage of 78%, with only 1 requiring ablation in the latest isochrone. Conclusions— Late potentials identified in the latest isochrone of activation during sinus rhythm are infrequently correlated with successful ablation sites for VT. The targeting of slow conduction regions propagating into the latest zone of activation may be a novel and promising strategy for substrate modification.